[Paid ambushes ; Destruction of Mines View Park ; Norman Black [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
An investigative look at BBC newsman's revelation that ambuses can be staged for a fee. Ecological/political story of city planning gone haywire in a national park in Baguio City. A look at basketball "imports" in Philippine basketball league.
Paid ambushes (13 min.) -- Destruction of Mines View Park (18 min.) -- Norman Black (10 min.)
VHS.
Keywords: Black, Norman; Foreign correspondents -- Philippines; Basketball players -- Philippines -- Interviews; Journalism -- Philippines; Mines View Park (Baguio City).